Numerical Method for the Deformation Calculation of the Shallow Buried Tunnel Caused by the Excavation of Overlying Soil Based on Soil Rebounding Characteristics - Li, Jian; Li, Shichang; Zhang, Yu; Chen, Shanxiong; Yu, Fei; Dai, Zhangjun; Li, Chaoxiong (Frontiers in Earth Science, 2022)
In view of the strict deformation control standard, it is important to calculate the shallow tunnel deformation caused by the unloading of overburden soil for analyzing the tunnel structure safety. Due to the obvious nonlinear characteristics and the significantly smaller rebound deformation of soil under unloading condition, the previous numerical calculation methods need to be improved to adapt to the soil deformation characteristics under unloading. Based on the above knowledge, cyclic loading and unloading tests were carried out to study the deformation characteristics of soil under different load levels, stress history and unloading levels. Secondly, a unified modulus calculation model is established, especially for the unloading modulus, which can consider the unloading stress history and current unloading stress level, providing a basis for the value of soil modulus in different states. Then, the relationship between the unloading rebound modulus Esc and the rebound modulus Ec0 used in the numerical simulation is studied. Finally, a set of numerical calculation and analysis method for shallow tunnel deformation caused by overlying soil excavation based on its rebounding characteristics is proposed. The rationality of the method is verified by two examples, and it is applied to a practical project.